The Psychological Condition of the Main Character in Devia Ananda's Novel Hey, Bodyguard! (A Secret): Carl Rogers' Humanistic Perspective - Febriani Khalimatus Sa'diyah; Hespi Septiana (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study is to describe the psychological condition and fulfillment of Rogers' humanistic concept of Rayyan in the novel Hey, Bodyguard! (A Secret) by Devia Ananda. This study raises the important issue of mental health in the process of individual development. This study uses a qualitative method with a literary psychology approach to process the data. The descriptive technique with data analysis procedures uses five aspects of Carl Rogers' humanistic psychology, namely self-concept, ideal self, unconditionally positive regard, fully functioning person, and empathy. The source of research data is the novel Hey, Bodyguard! (A Secret) by Devia Ananda, published in 2023 by Sunset Road, with data in the form of relevant narrative and dialogue excerpts related to the research focus. The data collection technique involved reading, identifying the main character's research focus, marking dialogues or narratives, collecting data, and categorizing data. The data validity technique used triangulation to validate the objectivity of the research. The results of the study show two psychological disorders, namely post-traumatic stress disorder and psychosis. Rayyan's self-concept shows that he is vulnerable due to psychological symptoms such as dull affect, excessive feelings of uselessness, emotional instability, and distortion of reality. His ideal self is centered on family values, apologies, and psychological healing. The unconditionally positive regard Rayyan receives takes the form of acceptance, attention, support, and motivation. Rayyan is not a fully functioning person, but his empathy has been reactivated.